Difference in knowledge and attitude of students towards medical ethics in preclinical and clinical phases of medical course in Gandaki Medical College, Pokhara - Hirachan, Neelu; Atreya, Alok; Kanchan, Tanuj; Shrestha, Nirmala (Journal of Kathmandu Medical College, 2020)
Background: Medical ethics is a core component in the standardization of medical practice of any nation. Due to this reason, knowledge related to this subject should be imparted to the medical students. Only then, the aim of providing a strong base in the medical field and making of an ideal doctor will be possible. Objective: The study was conducted to compare the status of knowledge and attitude of medical ethics before and after the medical ethics theory class among medical students of Gandaki Medical College, Pokhara. Methodology: This was a cross sectional study conducted in Gandaki Medical College, Pokhara from 1st to 31st August, 2018. A total number of 232 medical students were divided into two groups depending on whether they had attended medical ethics classes or not. Five point Likert scale was used in the responses of the participants and analyzed. Results: The study found that there was significant difference between two groups regarding the importance of consent for all minor operations (p=0.010), general physical examination (<0.001), genital examination of males (p<0.001) and females (p<0.001), treatment of children and adults in emergency and non-emergency without their consent. Similarly, students after medical ethics class compared to the ones not having attended any class strongly disagreed that euthanasia is legalized in Nepal (p-value<0.001). Conclusion: Students after medical ethics theory class had a better understanding of medical ethics compared to the students who did not. Furthermore, active teaching methods like group discussions, role play and pedagogy can be incorporated to have a more effective impact on the students.